Geste, matière et numérique - Maud Mulliez (In Situ)
3D imaging has become an essential tool in archaeology. Digital acquisition of remains and 3D restitution based on several hypotheses have both a demonstrative interest and a research goal. And it is as much efficient when it is not dissociated from materiality, but rather if it takes it into account. This paper presents some examples that illustrate the advantage of combining digital experience with practice. It shows how useful it is to combine digital and materiality in art history and archaeology using both digitisation of an object and its 3D printing, or using material experimentation to provide better results in digital reconstructions in sculpture and architecture.Another kind of archaeology can be mentioned, one that deals with gesture. In this field, digitisation and 3D are also of particular interest. Our project “L’Empreinte du geste” selected by the IDEX of Bordeaux as part of its Arts and Sciences program is dedicated to this research. Trying to rediscover the gesture and tools that have produced it with the help of an archaeological trace: that was the starting point of the project, carried out in collaboration with the INRIA at Bordeaux and the Institut d’optique d’Aquitaine. Still in its exploratory phase, our proposal aims at analysing the correlations between gesture and traces thanks to a motion capture system (using a set of markers OptiTrack) and the digitisation of the piece of work created.